Cytocompatibility, bioactivity and mechanical strength of calcium phosphate cement reinforced with multi-walled carbon nanotubes and bovine serum albumin - Gholami, Fatemeh; Zein, Sharif Hussein Sharif; Gerhardt, Lutz Christian; Low, Kah Ling; Tan, Soon Huat; McPhail, David S.; Grover, Liam M.; Boccaccini, Aldo R. (Ceramics International, 2013)
This paper reports on the in vitro cytotoxicity, bioactivity behaviour and mechanical properties of novel injectable calcium phosphate cement filled with hydroxylated multi-walled carbon nanotubes and bovine serum albumin (CPC/MWCNT-OH/BSA). To predict the in vitro bioactivity of the calcium phosphate composites, we investigated apatite formation on CPC/MWCNT-OH/BSA composites after soaking in simulated body fluid (SBF) for up to 28 days. Compressive strength tests, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and cell culture experiments with human CCD-18Co fibroblasts cell lines were performed to evaluate the effect of SBF pre-treatment on the mechanical, structural and biological properties of the CPC/MWCNT-OH/BSA composites. Although apatite formation increased significantly with SBF immersion period, the results showed that all soaked CPC/MWCNT-OH/BSA composites exhibited up to 2.5 times lower compressive strength (13-20 MPa), which were however higher than values reported for the strength of trabecular bone (2-12 MPa). Cell culture experiments showed that low concentrations (6.25 and 12.5 μg/ml) of bio-mineralised CPC/MWCNT-OH/BSA composites led to cell proliferative rather than cytotoxic effects on fibroblasts, evidenced by high cell viabilities (104-113%). The novel CPC/MWCNT-OH/BSA composites presented in this study showed favourable cytocompatible and bioactive behaviour along with high compressive strength (13-32 MPa) and are therefore considered as an attractive bone filling material. © 2012 Elsevier Ltd and Techna Group S.r.l.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.cytoco
Keywords: Compressive strength; CPCs; Cytotoxicity; In vitro bioactivity